Pengaruh Promosi dan E-Service Quality terhadap Minat Beli Ulang Penggunaan Gopay - Felien Putri Tunggadewi; Hery Pudjoprastyono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research aims to analyze: The effect of promotion and E-Service Quality on the interest in buying backs using Gopay. The population used in this study is consumers who have used GOPAY. The study used primary data using questionnaires distributed to 70 respondents from consumers who had used GOPAY. This study used questionnaire data collection methods with non-probability sampling / nonrandom sampling techniques. In this study, the data analysis used is a component-based Structural Equation Modeling (SEM) Method using the Least Square partial analysis tool (PLS). The results of this study show that promotion has an effect on the interest of GOPAY consumer repurchase. qulity e-service affects GOPAY consumer repurchase interest Keywords: Promotion; E-Service; Re-buy Interest, Gopay